354. Evidence of Aspergillosis Among Patients With Influenza-Associated Hospitalizations—United States, 2005–2017. (26th November 2018) - Toda, Mitsuru; Beer, Karlyn; O'Halloran, Alissa; Reingold, Arthur; Alden, Nisha; Yousey-Hindes, Kimberly; Anderson, Evan J; Bohm, Susan; McMahon, Melissa; Butler, Lisa; Pradhan, Eva; Felsen, Christina B; et al.
Abstract: Background: Invasive aspergillosis primarily affects immunosuppressed persons, but it has also been observed in immunocompetent patients with severe influenza. Several case series suggest that severe influenza infection might be an under-recognized risk factor for aspergillosis. We examined the frequency of aspergillosis-related hospital discharge codes in a national surveillance database of influenza hospitalizations. Methods: We analyzed laboratory-confirmed influenza-associated hospitalizations reported during 2005–2017 to Centers for Disease Control and Prevention (CDC)'s Influenza Hospitalization Surveillance Network (FluSurv-NET), which includes children and adults in 13 states. We obtained data on underlying conditions and clinical course through medical chart abstraction. We defined invasive aspergillosis cases as influenza hospitalizations with ≥1 of the following the International Classification of Diseases (ICD) 9th or 10th Clinical Modification discharge diagnosis codes: 117.3 (aspergillosis), 484.6 (pneumonia in aspergillosis), B44.0 (invasive pulmonary aspergillosis), B44.2 (tonsillar aspergillosis), and B44.7 (disseminated aspergillosis). Results: Among 92, 671 influenza hospitalizations, we identified 94 cases (0.1%) that had invasive aspergillosis codes. Characteristics of patients were: 60% male (56/94), 72% white race (60/83), and median age 58 years [interquartile range (IQR) 41–67]. Influenza A accounted for 80% (75/94) of cases. Seventy-nine percent (74/94) received antiviral therapy. Underlying conditions included 63% (59/94) immunocompromising condition, 51% (48/94) chronic lung disease, 22% (21/94) renal disease, and 15% (14/94) asthma. Forty-eight percent of patients (45/94) required intensive care. At the time of discharge, 60% (56/94) were diagnosed with pneumonia and 14% (13/94) died. Conclusion: Over one-third of patients with invasive aspergillosis did not have a documented immunosuppressive condition. ICD codes are likely an imperfect way to identify invasive aspergillosis, and further studies are needed to characterize risk factors and verify diagnoses for aspergillosis among patients with severe influenza. Disclosures: E. J. Anderson, NovaVax: Grant Investigator, Research grant. Pfizer: Grant Investigator, Research grant. AbbVie: Consultant, Consulting fee. MedImmune: Investigator, Research support. PaxVax: Investigator, Research support. Micron: Investigator, Research support. K. Talbot, sanofi pasteur: Investigator, Research support. Gilead: Investigator, Research support. MedImmune: Investigator, Research support. Seqirus: Scientific Advisor, Consulting fee. MedImmune: Scientific Advisor, Consulting fee.